Thessaloniki Metro: Public satisfaction in relation to the progress of the construction works - Zoumpoulis Dimitrios; Demertzidis Ypatios; Palantzas Georgios; Nalmpantis Dimitrios (E3S Web of Conferences)
The Thessaloniki Metro project is a significant transportation initiative with profound economic and environmental implications. This study evaluates public satisfaction with the project’s construction progress. Initiated in 2003, the Thessaloniki Metro aims to enhance urban mobility and safety while reducing travel time and environmental impacts. The survey, conducted through Google Forms, included 108 participants, predominantly young citizens. Key findings indicate a strong public endorsement of the metro’s construction, with 85.1% rating it positively. However, there is widespread dissatisfaction regarding project delays attributed to bureaucracy, legal complications, and inefficient fund management. Notably, 99.1% of respondents acknowledged significant delays, and 61.7% reported diminished trust in state institutions due to these setbacks. Despite these issues, there is optimistic support for network extensions, particularly towards Kalamaria and the Thessaloniki Airport “Macedonia.” Economically, 83.2% of participants are willing to use the metro if ticket prices align with those in Athens. The study concludes with recommendations for addressing delays and suggests future surveys post- completion to assess changes in public satisfaction. The findings highlight the need for timely project completion to meet public expectations and improve urban transit infrastructure.